Development and exergo-energetic analysis of an energy-efficient solar-assisted transcritical CO2 refrigeration system with two-phase ejector - Orelien T. Boupda; Frederic Lontsi; Thomas Djiako; Roger Ekani (Energy Conversion and Management: X)
This paper proposes and evaluates the performance of a new refrigeration and energy production system that combines the vapor compression cycle with ejector and the Brayton subcycle using CO2 as the working fluid. In this system, the Brayton cycle uses solar radiation as thermal energy, the heat of which is transmitted to the fluid through a solar concentrator, then expanded in a turbine to produce mechanical energy favorable to the reduction of energy consumed by the compressor of the refrigeration cycle. The study aims to examine the energy and exergy performance criteria of the combined system. The developed model of the system was simulated using EES software, for an evaporation temperature of −10 °C and a cooling capacity estimated at 15 kW. The analysis of the system in case of solar radiation, presents a COP of 2.88, an improvement of 30.05 % compared to the conventional system, with an exergy efficiency of 25.6 %. In addition, the effect of several operating parameters on the system performance are discussed, including solar irradiation, mass flow fraction, ambient temperature and evaporation temperature. Simulation results show that the energy savings of the proposed system can reach a threshold value of 43 % for a mass flow fraction α = 0.9 or at a maximum solar irradiation of 1000 W/m2.